Factors that influence the language and communication of hearing-impaired children - Ramkalawan, Tina Winnie (1996)
Studies have shown that permanent childhood hearing impairment can have detrimental consequences for spoken-language development. It is widely accepted that early detection and intervention may improve outcomes for profoundly hearing-impaired children. However, few studies evaluate the influence on the families or give particular attention to children with mild-to-severe hearing impairments.